HETEROCHRONOUS CENTERS OF NAPHTHIDE FORMATION AND ACCUMULATION IN THE NORTH-ASIAN CRATON - Kontorovich A.E.; Bakhturov S.F.; Basharin A.K.; Belyaev S.Yu.; Burshtein L.M.; Kontorovich A.A.; Krinin V.A.; Larichev A.I.; Guodu L.; Melenevskii V.N.; Timoshina I.D.; Fradkin G.S.; et al. (My University, 1999)
The paper gives the definition of the North-Asian craton as a geological structure. The evolution of conception and views of its structure and boundaries is considered, and a brief overview of its geologic history in terms of the present-day geodynamic concepts is given. The formation of sea and ocean basins in the craton margins is shown to be heterochronous. The main stages of accumulation are considered, and the geochemical characteristics of the main oil-generating strata are presented. It is evident that at least in the Riphean and Early Paleozoic the strata extremely rich in aquagenic organic matter accumulated mainly on passive and active continental margins. The role of the Triassic rifting in the formation of the Mesozoic sedimentary basins is discussed as well as the influence of trappean magmatism an the petroleum potential of the North-Asian craton. It has been determined that the center of oil and gas generation is part of a sedimentary basin, the section of which contains organic-rich sedimentary sequences intensively subsiding into the main zones of oil and gas generation during the geologic history. Characteristics of the main stages of formation of oil and gas generation centers, their migration in time, and the periods of oil and gas generation in them ate presented. The relationship between the centers and large zones of oil and gas accumulation is shown. Geochemistry of oils formed at individual centers of oil and gas generation and distribution of saturated biomarker hydrocarbons are considered. Oils have been distinguished as marine and nonmarine. The formed have been divided into several families. Particular emphasis has been placed on the description and specific character of Precambrian oils.
Keywords: Precambrian; Mesozoic; Triassic; Paleozoic; Riphean; Докембрий; Paleozoic; Докембрий::Протерозой::Рифей; Precambrian::Proterozoic::Riphean; Мезозой; Мезозой::Триасовая; Mesozoic; Mesozoic::Triassic; Палеозой; Precambrian